24 European etnographic museums - Van der Heide, Sara ([S.l.] : Idea Books, 2011)
’24 European Ethnographic Museums’ is a publication on a work with the same title by Sara van der Heide. This work consists of a series of 24 drawings that show the Western obsession with the categorization and conservation of artefacts and people. Van der Heide’s series becomes a collection of artefacts in and upon itself by recording the names of European ethnographic institutions. This publication includes the story ‘The Museum of Western Folklore: A Commemorative Speech’, written by Moosje Goosen in conjunction with the work of Van der Heide.
boek
Keywords: Van der Heide, Sara